Giant Cell Tumor of Tendon Sheath Developed over Chimeric-Free Latissimus Dorsi and Serratus Anterior Muscle Flaps - Karonidis, Athanasios; Kostopoulou, Akrivi; Pappa, Sofia; Tsoutsos, Dimosthenis (Journal of Hand and Microsurgery, 2019)
This article describes a rare case of giant cell tumor of the tendon sheath (GCTTS) that was developed over the substance of chimeric-free latissimus dorsi and serratus anterior muscle flaps performed for lower limb reconstruction. To our knowledge, development of GCTTS over a free flap is first described in the literature. A 71-year-old woman was presented with a large protuberant ulcerated tumor mass that was developed over the substance of chimeric free muscle flaps at the foot and ankle. We performed an extensive tumor resection, and the pathology report confirmed the presence of a primary giant cell tumor. The patient was advised to have a below-knee amputation. However, the patient refused the amputation, and 4 months later, she was presented with a metastatic mass proximally at the upper thigh. We believe that the GCTTS was associated with the chronic inflammation of the soft tissue and bones along with the recurrent episodes of infection, mainly due to proteus mirabilis and proteus syndrome (PS). PS may lead to the development of malformations and overgrowth of different tissues in unusual locations. In cases resistant to antibiotics, the radical surgical debridement should be considered as the most effective treatment.
Keywords: giant cell tumor of tendon sheath; proteus syndrome; chimeric-free flap; microsurgery